2020
DOI: 10.1080/10645578.2020.1776562
|View full text |Cite
|
Sign up to set email alerts
|

Designing 3-D Prints for Blind and Partially Sighted Audiences in Museums: Exploring the Needs of Those Living with Sight Loss

Abstract: How to cite:Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
9
0
2
Order By: Relevance
“…Whole prints of the tsantsa could be carried out where aspects such as opacity, heaviness, and overall accuracy are varied to help confer the actual qualities of the original specimen. Studies in the literature that attempt to understand what a typical museum-going audience might prefer in a replicated artifact demonstrate clearly that "verisimilitude" (the closeness of the printed model compared to the authentic artifact) is the quality of highest preference [29,34,35]. In total, the CTscan and corresponding SLA print generated here allows assessment of 12 out of 33 characteristics required for authentication.…”
Section: D Printed Replica From Ct Scanmentioning
confidence: 95%
“…Whole prints of the tsantsa could be carried out where aspects such as opacity, heaviness, and overall accuracy are varied to help confer the actual qualities of the original specimen. Studies in the literature that attempt to understand what a typical museum-going audience might prefer in a replicated artifact demonstrate clearly that "verisimilitude" (the closeness of the printed model compared to the authentic artifact) is the quality of highest preference [29,34,35]. In total, the CTscan and corresponding SLA print generated here allows assessment of 12 out of 33 characteristics required for authentication.…”
Section: D Printed Replica From Ct Scanmentioning
confidence: 95%
“…All of the artifacts were printed straight from the archive of the Scan the World project. A recent study [ 23 ] revealed that many museum visitors who are BPS favor non-alteration in 3D printed objects and want to handle an accurate replica. Alteration is considered to be problematic because it can negatively affect user interpretations [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…A recent study [ 23 ] revealed that many museum visitors who are BPS favor non-alteration in 3D printed objects and want to handle an accurate replica. Alteration is considered to be problematic because it can negatively affect user interpretations [ 23 ]. To stay as true as possible to the original forms, the artifacts were not altered and kept original features such as surface cracks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations